Fingerprint-Based Student Attendance System at SMP Negeri 3 Sitiung: Sistem Absensi Siswa Berbasis Fingerprint pada SMP Negeri 3 Sitiung - Heri Sudibyo; Nisa Mariana; Fauzi Tri Yuniko (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
Student attendance systems are an important component in supporting administrative activities in schools. Attendance processes that are still carried out manually have several limitations, such as the potential for recording errors and the time required for implementation. Therefore, this study aims to design and develop a fingerprint-based student attendance system at SMP Negeri 3 Sitiung. The method used in this study is the prototype method, which includes the stages of system design, development, and testing. The system uses ESP32 as the main microcontroller integrated with the AS608 fingerprint sensor, RTC DS3231 module, LCD, LED, buzzer, and WiFi connectivity with time synchronization support using the Network Time Protocol (NTP). The attendance data obtained are sent and stored in Google Sheets as an online-based storage medium. The results show that the developed system is capable of identifying students’ fingerprints, displaying attendance information, and automatically sending attendance data. In addition, the RTC module functions as a backup time source when there is a disruption in time synchronization through the network. Thus, the system supports integrated recording of student attendance.